METODE PROBLEM SOLVING DALAM PEMBELAJARAN PAI - Mindani Mindani (Jurnal Educative: Journal of Educational Studies, 2016)
Abstract The learning method has a crucial position in the learning process, because practically method of learning as the application of learning objectives. Islamic education (PAI) as a subject of study should be taught and assisted with learning approaches, including problem solving method, in this article, author will attempt to discuss analysis Islamic learning paradigm that viewed from the dimension of learning with problem solving method. From this discussion the author also cite the similar and relevant passages with the problem solving principle. Then the authors look at the opinions of leaders of Islamic and the general education about problem solving teaching concept, the results of this study the author can make assumptions as conclusion that the problem solving teaching principles and methods can be applied in Islamic education learning, because the core of Islamic education learning material sourced from Al -Qur'an and Sunnah are all filled with scientific gesture that should be applied with human reasoning and should provide the appropriate solution. Therefore, problem solving methods can be considered giving learning solutions in Islamic education. Keywords: Method, Problem solving, Learning PAI.